Situational analysis of pesticide poisoning and perceptions of autoinjector devices in rural communities in Sri Lanka – a study protocol - Janet Perkins; Alice Street; Upul Wickramasinghe; Manjula Weerasinghe; Michael Eddleston; Jane Brandt Sørensen (Global Health Action)
Intentional and unintentional pesticide poisoning is an important public health problem, especially in low- and middle-income countries. Individuals who have been exposed to toxic pesticides, particularly organophosphorus insecticides, need early treatment. Atropine autoinjector devices offer a potential solution, allowing storage of effective treatment near agricultural workers’ fields and homes that could be reached within minutes by the worker or fellow villagers to provide first-line emergency care. Here we present the design of a qualitative, formative study that will constitute the first phase of an implementation science study exploring the introduction of atropine autoinjectors in rural villages. This study will employ a qualitative design to investigate the feasibility and operational opportunities and challenges in providing pre-hospital emergency care with atropine autoinjectors in rural communities in Sri Lanka. We will conduct semi-structured interviews, ethnographic observations, oral history interviews, participatory mapping, and focus group discussions in villages and in hospitals. This study will allow the design of an autoinjector intervention that is tailored to specific needs of rural communities, maximise the potential benefits in the villages where they are placed, and contribute to knowledge related to biomedical technologies designed for use in LMICs. It will also contribute to social science scholarship in the context of pesticide poisoning. Study approvals have been obtained from the University of Edinburgh Medical School Research Ethics Committee (23-EMREC-039) and from Ethics Review Committee, Faculty of Medicine and Allied Sciences, Rajarata University of Sri Lanka (ERC/2023/4).